Molecular characterization and antiparasitic activity analysis of a novel piscidin 5-like type 4 from Larimichthys crocea. (January 2021) - Zheng, Libing; Qiu, Jiayin; Liu, Huihui; Shi, Huilai; Chi, Changfeng; Pan, Ying
Highlights: A novel Lc-P5L4 was identified and characterized. Lc-P5L4 was involved in the whole immune response against C. irritans . rLc-P5L4 owned peculiar antiparasitic activity to C. rirritans theronts. rLc-P5L4 could cause theronts aggregated and clumped, then cell membrane rupture and contents leakage. Abstract: Cryptocaryon irritans is an obligate parasitic ciliate protozoan that can infect various commercially important mariculture teleosts and cause high lethality and economic loss, especially Larimichthys crocea . Current methods of controlling or preventing this parasite with chemicals or antibiotics are widely considered to be environmentally harmful. The antiparasitic activity of some antimicrobial peptides (AMPs) attracted extensive attention of scholars. In the study, a novel piscidin 5-like type 4 (termed Lc-P5L4 ) excavated from comparative transcriptome of C. irritans - immuned L. crocea was identified and characterized. Sequence analysis shows the full-length cDNA of Lc-P5L4 is 539 bp containing an open reading frame (ORF) of 198 bp which encodes a peptide of 65 amino acid residues. The genome consists of three exons and two introns which exist in its ORF, and all the exon-intron boundaries are in accordance with classical GT-AG rule (GT/intron/AG). Multiple alignments indicate the signal peptides share highly conserved identity, while mature peptides are more diverse. Phylogenetic analysis displays Lc-P5L4 clusters together with other members of piscidin 5-like family. Next, quantitative Real-time PCR (qRT-PCR) detection found C. irritans infection could upregulate Lc-P5L4 expression level in all tested tissues significantly, it appeared earliest upregulation in the theronts infection stage in the head kidney; the expression contents reached to maximum level in the intestine, gill and muscle during trophonts falling off stage; while it was just upregulated during secondary bacterial infection stage in the liver and spleen. The data showed Lc-P5L4 upregulation time points were in accordance with different infection stages. With recombinant Lc-P5L4 (rLc-P5L4) obtained through Escherichia coli system, in vitro assay showed rLc-P5L4 could cause cilia deactivation, cell bodiesclumping and sticking to each other, then cell membrane rupture and contents leakage. The data illustrated Lc-P5L4 played critical roles in the immune defense against C. irritans infection, and provided another proof that piscidins exhibit multiple anti- C. irritans features.